Benefits and Drawbacks of Online Assessment (مجلة المنصور, 2022)
Assessment online has for a long time been seen as a coming use of computers in education. However, thereare reasons why it is still not fully used. At many universities around the world computers are used inexamination but only on intranet not online on Internet. The computers have been used instead of paper and pencil.This process has facilitated the collection of tasks solved or answered by students at the university. Making a finalexam or assessment online answering questions with the help of a computer from an arbitrary place outside auniversity is rare. Pre-tests,a study that helps to solve exam tasks and preparatory tests for joining a school oruniversity are quite common but passing a university course with only assessments online is not common. Wehave substituted parts of a final examination online and we are working on a full final examination procedure delivered only on the web.